Additional acute effects of virtual reality head-mounted displays on balance outcomes in non-disabled individuals: a proof-of-concept study - Eduardo de Moura Neto; Bruno Henrique de Souza Fonseca; Danilo Santos Rocha; Luciane Aparecida Pascucci Sande de Souza; Douglas Reis Abdalla; Dayane Aparecida Viana; Gustavo José Luvizutto (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aims to evaluate the additional acute effect of virtual reality (VR) head-mounted displays (HMD) when associated with balance exercises in balance outcomes in non-disabled individuals. Methods: Thirty individuals were randomized into two groups: balance exercise group (GBE; n = 15); and virtual reality + balance exercise group (GVR + BE; n = 15). The individuals were evaluated by static and dynamic balance using the tandem test (TT), single-leg stance (SLS), and Fukuda stepping test (FST). Both groups performed 30 min of balance exercises. The GVR + BE performed 8 additional minutes of virtual reality prior to balance exercises. A roller coaster application was used for the HMD. The Mann-Whitney test was used for intra-group and differences of inter-group analysis, considering a significance level of p < 0.05. Results: In the GBE group analysis, there was observed an increase of time in TT with closed eyes (p = 0.025) and SLS with closed eyes (p = 0.003). In the same way, the GVR + BE group increase TT with closed eyes (p = 0.003) and SLS with closed eyes (p = 0.002) after the intervention. In the intergroup analysis, the increase in the SLS with closed eyes was superior in the GVR + BE group when compared with GBE (p = 0.006; d = 1.67). Conclusion: The use of HMD in combination with balance exercise has an acute effect on increasing static balance in non-disabled individuals.